2015
DOI: 10.1016/j.jgr.2014.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Korean Red Ginseng supplementation on dry eye syndrome in glaucoma patients – A randomized, double-blind, placebo-controlled study

Abstract: BackgroundMany patients with glaucoma have difficulty using antiglaucoma eye drops because of dry eye symptom. In this prospective, randomized, double-blind, placebo-controlled study, we evaluated the effect of Korean Red Ginseng on dry eye syndrome in patients with glaucoma treated with antiglaucoma eye drops.MethodsForty-nine participants were allocated to the Korean Red Ginseng (3 g/day; n = 24) or placebo (n = 25) groups for 8 weeks. Tear film stability, fluorescein corneal staining, conjunctival hyperemia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 57 publications
2
13
0
Order By: Relevance
“…Recently, in a randomized, double-blind, placebo-controlled study, Bae et al 35 reported that Korean red ginseng supplementation given for 8 weeks significantly improved tear film stability and total ocular surface disease index score in patients with glaucoma and established topical hypotensive therapy, confirming the previous findings of an earlier study performed by the authors. 36 Ginseng (the root of Panax ginseng ) contains a variety of active components, including ginsenoides, polysaccharides, peptides, polyacetylenic alcohols, and fatty acids.…”
Section: Discussionsupporting
confidence: 73%
“…Recently, in a randomized, double-blind, placebo-controlled study, Bae et al 35 reported that Korean red ginseng supplementation given for 8 weeks significantly improved tear film stability and total ocular surface disease index score in patients with glaucoma and established topical hypotensive therapy, confirming the previous findings of an earlier study performed by the authors. 36 Ginseng (the root of Panax ginseng ) contains a variety of active components, including ginsenoides, polysaccharides, peptides, polyacetylenic alcohols, and fatty acids.…”
Section: Discussionsupporting
confidence: 73%
“…Scleral lens device to maintain a reservoir of tears to wet and lubricate the ocular surface 267,268 Acupuncture Possible effects on dry eye signs and symptoms, as compared to sham-treated controls or artificial tears [269][270][271] ShengJinRun ZaoYangXue granules Improve tear flow and reduce dry eye symptoms 272 Korean red ginseng Improve tear film stability and reduce dry eye symptoms 273 Suppressing transient receptor potential vanilloid 1 (TRPV1) receptor Trefoil factor family peptide 3 (TFF3) Stabilize mucous layer 279,280 Nerve growth factor & mimetics Increase goblet cell number and MUC5AC production; increase corneal sensitivity; promote corneal epithelial wound healing 281,282 Tamarind seed polysaccharide Mimic the mucoadhesive mucin properties [283][284][285][286] Nanoparticles Deliver plasmids coding for MUC5AC protein to the ocular surface 287,288 M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 294,295 Salivary gland transplantation Replace dysfunctional lacrimal gland [296][297][298] Generation of two-and threedimensional lacrimal gland constructs for lacrimal gland regeneration Serve as bioengineered lacrimal gland replacement 299 Oculeve electrode device Stimulate the lacrimal nerve to induce aqueous tear production [300][301][302] Oral anethole triothine Increase Schirmer wetting score 303 Oral uridine Stimulate tear and mucin secretion after metabolism into P2Y2 agonist 304 Oral hydroxychloroquine Increase Schirmer wetting score in in Sjögren's syndrome patients with anti-fodrin antibodies 305 Oral pilocarpine and cevimeline Reduce subjective eye symptoms in Sjögren's syndrome patients, with no effect on tear volume [306][307][308] Lacritin...…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Many people who suffer from glaucoma and use associated medications complain of dry eye and have a higher prevalence of ocular surface disease than the general population [156,157]. The preservative within the drops (benzalkonuim chloride (BAK)) has been suggested as the cause of the reported associated inflammation, blepharitis and DED [158]. Red ginseng is a traditional folk remedy used in East Asia to treat a number of disorders including endocrine and immune disorders [158].…”
Section: Other Functional Foodsmentioning
confidence: 99%
“…The preservative within the drops (benzalkonuim chloride (BAK)) has been suggested as the cause of the reported associated inflammation, blepharitis and DED [158]. Red ginseng is a traditional folk remedy used in East Asia to treat a number of disorders including endocrine and immune disorders [158]. The chronic inflammatory association and goblet cells loss in DED are commonly treated with anti-inflammatory drugs.…”
Section: Other Functional Foodsmentioning
confidence: 99%
See 1 more Smart Citation